(untitled) (Swiss Medical Weekly, 2025)
STUDY AIMS:Community pharmacies serve as important partners in reducing the tobacco burden in the population by delivering effective smoking cessation interventions. This study depicts the current clinical practice of smoking cessation interventions in Swiss community pharmacies and assesses pharmacists’ attitudes towards integrating alternative nicotine delivery systems in smoking cessation interventions. METHODS: An interprofessional group developed and distributed an online survey to all community pharmacies affiliated with the Swiss Pharmacists’ Association. One pharmacist per pharmacy was invited to complete the survey. Surveys completed between 1 April and 9 May 2022 were used in the data analysis. Using R, the frequencies and proportions of the answers to the categorical questions were reported. To evaluate responses to questions rated on a 6-point Likert-type scale, the mean, standard deviation, and 95% confidence interval were calculated. RESULTS: Of the 1612 surveys distributed, 259 (16%) were completed. Most participants counselled their clients during nicotine replacement therapy sales (71%) or conducted brief opportunistic smoking cessation counselling (51%) at least once a month. Fewer than 21% of pharmacists offered dedicated smoking cessation counselling. Of the participating pharmacists, 69% recommended nicotine replacement therapies, and approximately 21% reported recommending e-cigarettes in some situations. By contrast, 90% reported never recommending tobacco heating systems, snus, or nicotine pouches. Pharmacists stated that a higher demand (mean = 4.78, standard deviation [SD] = 1.42 on a 6-point Likert scale), a decision aid (mean = 4.58, SD = 1.51), more training (mean = 4.39, SD = 1.43), financial compensation (mean = 4.35, SD = 1.63), and better collaboration with other healthcare professionals (mean = 4.25, SD = 2.13) would enhance the frequency of smoking cessation interventions. CONCLUSIONS: According to this online survey distributed to pharmacists in Switzerland, basic smoking cessation interventions are common, but counselling on smoking cessation could be intensified. Although Swiss pharmacists are currently reluctant to offer alternative nicotine delivery systems as smoking cessation aids, they show interest in receiving training on such products. Greater financial incentives, targeted campaigns, clear decision aids, and improved interprofessional collaboration could help strengthen future smoking cessation interventions in Swiss community pharmacies.